Effect of zinc plating of low carbon steel on corrosion resistance in cocoa fluid environment (2008)
"This work investigated the corrosion resistance of zinc-plated low carbon steel in cocoa fluid. Low carbon steel samples were zinc electroplated at voltages between 0.5 V and 0.9 V for 5–20 min. The plated samples were then subjected to a cocoa fluid environment for 30 days. The electrode potentials mV (SCE) were measured every day. Weight loss was determined at intervals of 5 days for the exposure period. The result showed corrosion attack on the zinc-plated steel, the severity increasing with the increasing weight of zinc coating on substrate. The result showed that thinly plated low carbon steel generally did not have any advantage over unplated steel. Heavily zinc plated steel was observed to offer some form of protection for the plated steel as passivation was observed to occur on the nineth day of corrosion leading to almost nil corrosion rate. The pH of the cocoa solution which initially was acidic was observed to progress to neutral after 5 days, contributing to the near nil corrosion rates in the plated samples after 15 days. It was observed that electroplated steel plate at 0.8 V for 5 min and the more heavily plated steel at 0.9 V for 10 min gave the best resistance to cocoa fluid corrosion attack in the 30 days test period. Unplated steel was found to be unsuitable for the fabrication of cassava processing machinery without some form of surface treatment. "